Building A Work Culture in Efforts to Improve Employee Performance PT. X - Jihaan, Anisa; Sugiyanto, Eviatiwi Kusumaningtyas (Universitas Semarang, 2020)
This study aims to determine work culture in an effort to improve employee performance at PT X. This research is a qualitative research with a case study approach. Collecting data in this study using triangulation of data sources, namely observation, interviews, and documentation. Six informants were selected based on the principle of suitability(appropriateness) and sufficiency (adequacy).The results showed that PT X's work culture had benefits, namely the formation of a good work process, a more structured job, a faster problem-solving process and increased human resource capabilities. while the barriers in work culture are a lack of confidence, busy daily routines, inefficient organizational structure, lack of motivation and competence, lack of cohesiveness and employees who do not upgrade their abilities or knowledge.